Effects of Hepatitis B Immunization Completeness on Hepatitis B Incidence among Children in Indonesia - Faisal; Nurhayati Adnan Prihartono (Future Science, 2023)
Indonesia is a country that is endemic for Hepatitis B, with a prevalence of 7% to 10%. At least 3.9% of pregnant women in Indonesia are living with Hepatitis B, with a risk of maternal transmission of approximately 45%. The low coverage of hepatitis B immunization in infants aged 0–7 days can have an impact on increasing the prevalence of the hepatitis B virus. This study aims to determine the effect of immunization on the incidence of Hepatitis B among children in Indonesia. A cross-sectional study was conducted using the 2018 Basic Health Research (Riskesdas) data. The sample in this study was 7,434 children aged 6–12 months, excluding missing data. This study used univariate analysis to describe the general characteristics of the sample and bivariate analysis (Chi-square test) to examine the factors associated with hepatitis B with a 95% confidence interval. The results showed that there was no relationship between the complete administration of Hepatitis B immunization and the incidence of Hepatitis B in children (p-value = 0.351). The limitations of the Riskesdas data were that there was missing information about the immunization status of children, thus affecting the results of statistical tests related to the effect of HB immunization on the incidence of hepatitis B in children. Complete hepatitis B immunization coverage needs to be increased by taking into account various factors such as family support, family history of hepatitis B, age, level of education, knowledge, number of children, and the role of health professionals.